P134 BEYOND THE "BIG PICTURE": CAN MICRONUTRIENTS IMPACT SURGICAL OUTCOMES IN IBD?. (18th January 2018) - Gudsoorkar, Vineet; Ibarra, Sergio; Gonzalez-Almada, Alberto; Oglat, Ayah; Koduru, Pramoda; Haas, Eric; Abraham, Bincy
Abstract: Background: Approximately 1/3rd of the patients with ulcerative colitis (UC) and 70% of those with Crohn's disease (CD) undergo surgery over their lifetime. Nutritional optimization is a cornerstone of successful surgical outcomes in inflammatory bowel disease (IBD). Albumin and hemoglobin are the 2 most important laboratory markers used to estimate a patient's nutritional status, but the role of micronutrients in the surgical outcomes has not been widely studied. Methods: Fifty-one patients (34 CD, 17 UC) undergoing IBD-related surgery from 4/2015-4/2017 were retrospectively studied. Pertinent data were obtained. Surgical outcomes were measured as 30-day readmission rate, complications and need for post-operative blood transfusion. T-test and Chi-square test were used for analysis. Results: A statistically significant higher incidence of post-operative complications was seen in CD patients with low albumin (3.4 v 2.8 mg/dL). Clinical and endoscopic activity indices were higher in patients who had complications. Interestingly, deficiencies in vitamin D (<30 ng/mL) and zinc (<60 (μg/dL) had numerically higher incidence of post-operative complications, although not statistically significant. Preoperative albumin, iron and hemoglobin were significantly lower in patients that required postoperative blood transfusion. The outcomes were not statistically different when stratified by gender or use of preoperative steroids/immunomodulators. No such statistical associations were noted in the UC cohort, likely due to a low number of patients/complication rate. Conclusion: In addition to the routine markers of nutrition such as albumin and hemoglobin, micronutrient optimization should be an important consideration in patients undergoing IBD-related surgery. Vitamin D and Zinc play an important part in immune regulation and wound healing respectively, and may need larger prospective, controlled studies to assess their impact on surgical outcomes in IBD patients.